Evaluation of diets for mass rearing of the predatory bug Nesidiocoris tenuis (Hemiptera, Heteroptera, Miridae) - И. M. Пазюк (Вестник защиты растений, 2023)
Nesidiocoris tenuis (Hemiptera, Miridae) is a predatory bug which is widely used in biocontrol. This bug can consume both plant and animal matter. In the present paper, three alternative diets were evaluated in mass rearing of nymphs of N tenuis maintained in cages on tobacco plants: eggs of the grain moth Sitotroga cerealella, cysts of Artemia salina, and bee-collected pollen. Adults of N tenuis were fed a mixture of grain moth eggs and pollen during oviposition. The type of diet did not effect the survival of nymph. Output of adults was higher when nymphs were fed grain moth eggs than Artemia cysts while the body weight of adult bugs did not differ.